Tourism Development and Economic Growth in Bangladesh: New Evidence from Nonlinear Autoregressive Distributed Lag - Khan, Abdul Mahidud; Amin, Sakib Bin; Ahmed, Adib; Sultana, Tanzila (International Journal of Economics and Financial Issues, 2021)
We examine the long-run relationship between tourism development and economic growth using the Nonlinear Autoregressive Distributed Lag (NARDL) model for Bangladesh using annual data from 1980-2016. We find an asymmetric relationship between tourism and Bangladesh’s economy since a one percent increase in tourism receipt increases economic growth by about 0.19 percent. On the contrary, due to a one percent decline in the tourism receipt, economic growth will decrease by about 0.66 percent. So, the decline in tourism receipt will have a higher negative impact on economic growth than the increase in the tourism receipt in Bangladesh, which result is important for current pandemic situation in tourism due to Covid-19. We also reveal that the impact of positive change in the tourism revenue on GDP stabilizes around 8 years; however, an adverse change on GDP does not stabilize in 15 years. We recommend that a systematic allocation of resources is required to promote and stimulate the tourism industry in Bangladesh for a favourable impact on the country’s long-run economic development. Keywords: Tourism Development; Economic Growth; NARDL; Bangladesh; Asymmetry JEL Classifications: C32, O50, Z32 DOI: https://doi.org/10.32479/ijefi.11040